CZYM CHARAKTERYZUJE SIĘ POWOŁANIE KAPŁAŃSKIE W ROZUMIENIU ŚW. JANA PAWŁA II? - PASTEWSKI, Przemysław (Civitas et Lex, 2015)
This article show us about vocation according to Saint John Paul II. Pope said that every people has another vocation. Everyone has not the same vocation. One of us has vocation to priesthood, another to marriage. No matter which vocation we have, all of us should aspire to holiness. We should realize our vocation, in our daily life.